Closure of a large nasal dorsum defect using a bilateral crescent advancement flap from the malar region to the nose - Khairuddin Djawad; Idrianti Idrus; Airin Nurdin Mappewali (Sociedade Brasileira de Dermatologia (SBD), 2021)
The closure of large defects on the nasal dorsum is a challenge for dermatologic surgeons. The alternatives to repair the defect are a skin graft and some forms of skin flaps. One particular defect closure technique is the crescentic advancement flap, which uses crescent incisions at the nasolabial fold to accommodate the excess tissue. This flap is best used if the defect is in the lateral nose, alar, and nasolabial fold. We report a large defect of the nasal dorsum in a 65-year-old woman that was successfully reconstructed using bilateral cheek-to-nose crescentic advancement flap. The patient showed excellent cosmetic and outcome.